2016
DOI: 10.1186/s41182-016-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with diarrheal diseases among under-five children of the nomadic population in northeast Ethiopia

Abstract: BackgroundDiarrheal disease remains the leading cause of morbidity and mortality among under-five children worldwide. Every day, more than 4000 children lose their lives due to diarrhea. In Ethiopia, diarrhea is the second killer of under-five children next to pneumonia.MethodsA cross-sectional study was conducted to assess the prevalence of under-five diarrhea and socioeconomic factors among the nomadic people in Hadaleala District. A total of 704 under-five children were included in this study, and subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
67
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 22 publications
29
67
8
2
Order By: Relevance
“…Our study found that, the prevalence of diarrhea in children aged less than five years was 26.7%. This was similar to a study of 2-week period prevalence of diarrheal disease among under-five children conducted in Hadaleala District of Ethiopea which reported 26.1% [7]. The finding of this study is slightly lower than the finding of a study conducted in Burundi (32.6%) [15] and in Arba Minch District, Ethiopea (31.0%) [6].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our study found that, the prevalence of diarrhea in children aged less than five years was 26.7%. This was similar to a study of 2-week period prevalence of diarrheal disease among under-five children conducted in Hadaleala District of Ethiopea which reported 26.1% [7]. The finding of this study is slightly lower than the finding of a study conducted in Burundi (32.6%) [15] and in Arba Minch District, Ethiopea (31.0%) [6].…”
Section: Discussioncontrasting
confidence: 56%
“…In Ethiopia the prevalence of diarrheal disease among under-five children in a 2-week period was reported 31.0% in Arba Minch District [6], 26.1% in Hadaleala District [7], 24.9% in northwest Ethiopia [8], 22.5% in the eastern part of Ethiopia [9], 19.6% in a rural area of southern Ethiopia [10] and 18.0% in Mecha District [11]. There are different factors associated with occurrence of diarrhea among children less than five years and these differ from place to place.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the odds of developing childhood illness among children of semi-skilled/skilled mother occupational status were 2.3 times compared with unskilled mothers. This finding was in agreement with previous studies (37,(50)(51)(52). This can be justified in that maternal occupation and income are factors that provide information about the level of autonomy of the woman that could empower herself to take care of her child (53,54).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was noted a child lived in a family with three and/or more under-five children was more likely to have childhood illness than a household with only one child. This finding was supported with similar studies conducted elsewhere (36,(48)(49)(50). This could be explained by the fact that when the number of children in the household increases, it is expected that children could be more vulnerable to contamination because the quality of care and attention from parents decreases as mothers become incapable of caring for children.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, it was noted a child lived in a family with three and/or more under-ve children was more likely to have childhood illness than a household with only one child. This nding was supported with similar studies conducted elsewhere (36,(48)(49)(50). This could be explained by the fact that when the number of children in the household increases, it is expected that children could be more vulnerable to contamination because the quality of care and attention from parents decreases as mothers become incapable of caring for children.…”
Section: Discussionsupporting
confidence: 80%